(untitled) (Journal of Nepal Physical Society, 2021)
In the light of ongoing experimental search efforts for the dark matter and the post-Higgs Beyond the Standard Model (BSM) null results at the Large Hadron Collider (LHC), the Electroweak sector demands to be investigated for possible new scalar states discoverable at the LHC fulfilling the role of the dark matter. In this work we present a symmetric two Higgs doublet model with a discrete interchange symmetry among the two Higgs doublets (Φ1 ↔ Φ2). Apart from the Standard Model (SM)-like scalar state (h) with mh = 125 GeV, the model has several distinguishing features including the pseudoscalar (A), the charged scalars(H±) and the neutral scalar H, not having any direct coupling to the fermions. The neutral scalar H is assumed to have mass lighter than the 125 GeV SM-like Higgs state h. Due to the presence of a residual Z2 symmetry after the spontaneous symmetry breaking (SSB), the neutral scalar H can emerge as a viable dark matter candidate. We discuss the constraints on such scalar dark matter from the current direct and indirect detection experiments. As a by-product of this construction, the SM-like scalar h ends up having an extra invisible decay mode of h → HH in this model which can also influence the dark matter parameter space. We discuss these model features in detail along with a guideline of relevant phenomenological searches at the LHC for this scenario.